Green synthesis, crystal structure, and antifungal activities of (E)-4-arylidene-5-oxotetrahydrofuran - Dong, Yun; Kong, Ling-Qi; Chen, Qin-Hua; Li, Bin; Zeng, Xiao-Hua; Ke, Li-Na; Wang, Hong-Mei (Frontiers in Chemistry, 2022)
A series of γ-lactone derivatives (E)-4-arylidene-5-oxotetrahydrofuran derivatives were synthesized via a tandem Passerini 3CC/SN cyclization microwave-assisted one-pot method efficiently starting from Baylis Hillman acids, aryl glyoxals and isocyanides, and using ionic liquid as reaction medium. The products were characterized by hydrogen nuclear magnetic resonance spectroscopy (1H-NMR), carbon nuclear magnetic resonance spectroscopy (13C-NMR). Single crystal X-ray analysis of the compound RPDFB clearly confirmed its assigned chemical structures. Meanwhile, the effects of four compounds (RPDFB, RPDFC, RPDFI, RPDFJ) on the growth inhibition activity of Gibberella zeae were detected, and found that the compound RPDFB has significant growth inhibition activity to Gibberella zeae.